Design and development of an autonomous underwater vehicle for underwater target navigation mission module - Muhammad Muzakkir, Ahmad Rosian; Herda\vatie, Abdul Kadir; Khalid, Isa; Radzi, Ambar; Mohd Rizal, Arshad; Maziyah, Mat Noh; Mohd Helmy, Abdul Wahab (Springer Singapore, 2019)
The Autonomous Underwater Vehicles (AUV) industry is growing dramatically with the increase in the reliability and technical abilities of these vehicles. The vehicles require autonomous guidance and control system in order to perform underwater tasks. The Target Navigation Mission Module (TNMM) permits the vehicle to follow preprogrammed trajectories wherever and whenever required. Without this module, the vehicle will not be able to achieve the desired mission. In this work, the Mission module were able to identify the task, detect the target, coordinate the state of AUV (attain desired height and yaw angle) and makes decision on path based on mission time elapsed. The Target Navigation Mission Module used the Kalman Filter algorithm to estimates the state of a system during the navigation. The results shows a reliable reading obtain by the AUV. Therefore, better decision on motion direction \Vere achieved. The AUV was able to navigate underwater and track underwater object without the need of operator assistance.